The Role of Big Data in Circular Supply Chain Practices and Corporate Sustainability Performance - Fenisa, Dorotea; Santosa, Wahyuningsih (Universitas Bina Sarana Informatika, 2024)
The green industry is a national priority target, with one of the indicators being the application of a circular economy. The application of a circular economy to the entire supply chain process is an effort to extend the service life of materials so that sustainability arises. The application of circular supply chains needs to be supported by digital technology to improve processes. This study aims to analyze the effect of circular supply chain practices on corporate sustainability performance and the moderating effect of Big Data. The hypothesis testing using SEM analysis tools. The number of samples used was 140, who are currently working or have worked in companies that have implemented a circular economy. [KM1] The results of the study show that Circular Supply Chain Practices do not influence on Corporate Sustainability Performance, so the moderating effect of Big Data is not supported. Therefore, managerial parties need to implement a circular supply chain in the company's business processes. Managers need to provide technical training related to designing environmentally friendly products and educational strategies to customers regarding the application of a circular economy. Nonetheless, this study also has limitations, in that it consists of only one variable, Circular Supply Chain practices, which affect Corporate Sustainability Performance. Thus, the next researcher should add other variables that can affect Corporate Sustainability Performance, such as the purchasing realized absorptive capacity variable. [KM1]Refer in research method section for my comment.